THE IMPLEMENTATION OF MERDEKA CURRICULUM ASSESSMENT IN MEASURING LEARNING OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION AND CHARACTER EDUCATION AT SDN 6 PULUBALA, GORONTALO REGENCY - Daud, Firman; Otaya, Lian Gafar; Lestari, Anugrah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2025)
This study aims to analyze the implementation of assessment in the Merdeka Curriculum for measuring learning outcomes in Islamic Religious Education and Character Education at SDN 6 Pulubala, Gorontalo Regency. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation. The findings reveal that three types of assessments—diagnostic, formative, and summative—are applied. Diagnostic assessments help determine students’ initial competencies, formative assessments guide the learning process, and summative assessments evaluate learning achievements. Teachers have also developed instructional modules and lesson plans aligned with the principles of the Merdeka Curriculum. The appropriate implementation of these assessments has proven effective in enhancing the quality of learning and supporting students in achieving holistic educational goals. This study contributes to the discourse on curriculum implementation and serves as a practical reference for improving assessment practices in elementary education.